2018
DOI: 10.4067/s0718-33052018000100097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for predicting surface roughness in turning stainless steel AISI 316L

Abstract: The present study aimed to explore various models to predict the surface roughness in dry turning of AISI 316L stainless steel. Multiple Regression Methods and Artificial Neural Networks Methods were implemented to study the effect of cutting speed, feed, and machining time. In order to increase the reliability and soundness of the registered surface roughness values, a complete Factorial Design was implemented. A statistical comparison of the resultant models was performed. The results produced by both method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Much research and development has been carried out in the field of prediction and control of surface roughness using MV. Regarding the way of calculating the roughness parameters, these methods can be divided into analytical methods [7][8][9][10][11], where parameters extracted from images are correlated to the measured roughness by a mathematical function, and methods engaging artificial intelligence (AI) [12][13][14][15][16][17][18][19] to build the roughness predictive models.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Much research and development has been carried out in the field of prediction and control of surface roughness using MV. Regarding the way of calculating the roughness parameters, these methods can be divided into analytical methods [7][8][9][10][11], where parameters extracted from images are correlated to the measured roughness by a mathematical function, and methods engaging artificial intelligence (AI) [12][13][14][15][16][17][18][19] to build the roughness predictive models.…”
Section: Related Workmentioning
confidence: 99%
“…Morales Tamayo et al [18] used an ANN model to predict the steel surface roughness in the dry turning process of stainless steel. The researchers produced the specimens by varying the cutting parameters during the turning process.…”
Section: Related Workmentioning
confidence: 99%
“…An inverse relationship was observed for the effect of feed rate (FR). Tamayo et al [29] used artificial neural networks and multiple regression to predict the mean roughness of dry turning 316L steel using GC1115 and GC2015 inserts. It was found that decreasing the feed rate resulted in a reduction in the mean roughness Ra.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for better prediction values, some studies compare statistical methodologies to ANNs. Authors in [ 37 ] studied the AISI316L steel dry turning surface roughness prediction, by comparing ANNs to multiple regression methods. The results found by the methods indicate a better artificial neural networks accuracy.…”
Section: Introductionmentioning
confidence: 99%